Ground clutter simulation for airborne forward‐looking multi‐channel LFMCW radar. Issue 21 (23rd October 2019) - Li, Hai; Duan, Jialing; Song, Di
Abstract : Ground clutter is a crucial factor that affects the detection performance of the airborne forward‐looking multi‐channel linear frequency modulated continuous wave (LFMCW) radar, so the distribution characteristics of studying the ground clutter plays an important role in suppressing ground clutter and improving radar detection performance. In this article, the authors first use the Ward model to divide the effective clutter area into multiple independent clutter patches and calculate the echo signal of each clutter patch. Then the beat signal of each clutter patch is obtained by the de‐chirp processing. Next, a Fourier transform is performed on the beat signal of each clutter patch to determine the range ring where the echo of the clutter patch is located, and the peak spectrum signal of the beat signal of the clutter patch in the same range ring is superimposed, thus the authors can realise the simulation of the ground clutter signal. Finally, the simulation results indicate the effectiveness of the proposed method.